The metastasis associated protein S100A4: a potential novel link to inflammation and consequent aggressive behaviour of rheumatoid arthritis synovial fibroblasts - Oslejsková, L; Grigorian, M; Gay, S; Neidhart, M; Senolt, L (Annals of the rheumatic diseases, 2008)
The metastasis-associated protein S100A4 belongs to the large family of S100 calcium-binding proteins that appear to play regulatory roles in diverse biological activities. Moreover, a prognostic role of S100A4 has been suggested for patients with several types of cancer. Cancer promoting properties for S100A4 have been demonstrated, particularly through its regulation of cell motility, proliferation and apoptosis, as well as by stimulation of angiogenesis and remodelling of the extracellular matrix. Increased expression of S100A4 mRNA has been detected in proliferating synovial fibroblasts in rheumatoid arthritis. Furthermore, strong upregulation of the S100A4 protein in rheumatoid arthritis synovial tissue compared with osteoarthritis and control tissues has been demonstrated recently, especially at sites of joint invasion. Several immune and vascular cells were also identified to be producing S100A4 within the synovium. The local upregulation of S100A4 was accompanied by high plasma and synovial fluid concentrations of the S100A4 protein existing in the bioactive oligomeric form in patients with rheumatoid arthritis. Consistent with data from cancer studies, the extracellular S100A4 oligomer appears to be involved in regulation of several matrix-degrading enzymes and modulation of the transcriptional activation function of the tumour suppressor protein p53 in rheumatoid arthritis synovial fibroblasts. Taken together, one can speculate that increased S100A4 protein in circulation and locally at sites of inflammation, particularly at sites of joint destruction, might be linked to the process of aggressive fibroblast behaviour contributing to the pathogenesis of chronic autoinflammatory diseases such as rheumatoid arthritis.
Keywords: metastázy nádorů; zánět; proteiny S100; Arthritis, Rheumatoid; revmatoidní artritida; S100 kalcium vázající protein A4; Neoplasm Metastasis; Neoplasm Proteins; S100 Calcium-Binding Protein A4; Inflammation; Humans; S100 Proteins; Fibroblasts; nádorové proteiny; synoviální membrána; lidé; fibroblasty; Synovial Membrane